IMPACTS OF LAKE VICTORIA LEVEL FLUCTUATIONS TO LIVELIHOODS MISSUNGWI DISTRICT CASE STUDY - Kimaro, T. A.; Fidelis, R. (Tanzania Journal of Engineering and Technology, 2018)
Lake Victoria experienced drastic levels changes in 2005 causing great inconveniences to lakeside communities. This study investigated effects of these changes on livelihoods through questionnaire surveys, focused group discussions, interviews and analysis of fish catches, diseases, crops, and lake levels data. Results indicate recession of levels had various socio-economic impacts. The changes caused severe water shortage due to drying up of shallow wells and a remarkable increase in prevalence of schistosomiasis because of increased utilization of lake water. There was no evidence for impact of level changes on malaria and diarrhea. Decline of water levels caused decline in fish catches due to retreat of water from breeding sites. However receding waters created a new land for cultivation which helped to boost Maize and sweet potatoes production. The results emphasize on ensuring stability of lake levels to avoid negative impacts on livelihoods and to maintain ecological integrity of the lake.